Cause and Risk Factors of Delay Related to Neonatal Death in Afghan Immigrant Neonates Living in Tehran Province, Iran - Nahid Akbari; Leila Khedmat; Mansoureh Jamshidimanesh; Maryam Kashanian; Mohammad Javanbakht; Maziar Moradi-Lakeh; Ameneh Akhundi (Iranian Journal of Neonatology)
Background: Despite the global decline in neonatal mortality rates since 1990, reaching the Sustainable Development Goals (SDGs) targets by 2030 remains a considerable challenge. Three-quarters of infant deaths happen during the early infancy stage, influenced by fetal and maternal factors as well as health service readiness. Consequently, this period is crucial for mitigating the burden of infant mortality. Therefore, this critical period holds vital importance in alleviating the burden of infant mortality. Hence, the current study aimed to assess the factors contributing to early neonatal mortality, focusing on Afghan immigrant neonates and utilizing hospital information systems and medical records to identify potential determinants. Methods: Throughout a 21-month study period from 2017 to 2018, data was collected from 576 neonates, comprising 441 neonatal near-miss (NNM) cases and 135 neonates who died and were admitted to the neonatal intensive care unit across six selected hospitals. Data collection methods included thorough reviews of hospital systems and medical records and conducting telephone or face-to-face interviews using checklists and questionnaires. Statistical analysis was performed using SPSS version 20 for Windows, with a significance level set at P<0.05 and confidence intervals at 95%. A logistic regression model was employed for analysis, enabling control for confounding variables. Results about risk factors were presented as both unadjusted (crude odds ratio) and adjusted odds ratios (ORs) alongside corresponding 95% confidence intervals (CIs). Statistical significance was established at a p-value of ≤ 0.05. Results: Our data demonstrated that age of 20–35 (AOR = 1.394, 95% CI 1.209, 3.743; p = 0.005), mother's illiteracy [AOR 2.544, (95% CI, 1.316–6.498; p = 0.03)], newborn insurance [AOR 2.544, (95% CI, 2.387–10.656; p = 0.03)], risk factors of pregnancy [AOR 1.351, (95% CI, 1.833–5.978; p = 0.003)], number of pregnancies ≥ 5 [AOR 3.273, (95% CI, 2.083–10.84; p = 0.002)], 2-4 pregnancies [AOR 2.539, (95% CI,2.342–6.848; p = 0.007)], antenatal care [AOR 5.103, (95% CI,3.17- 056.901; p = 0.001)], gestational age [AOR 2.385, (95% CI, 2.322–9.652; p = 0.004)] and delay [AOR 3.178, (95% CI, 3.084–9.376; p = 0.001)] were linked to an increased risk of neonatal mortality. According to our findings, the first delay (delay in decision-making for care) was the most important delay factor involved in neonatal death, followed by the third delay (delay in receiving services) and the second delay (access to services). Conclusion: The elevated neonatal mortality rate (NMR) observed among Afghan neonates in Iran underscores their heightened vulnerability when compared to their Iranian counterparts. Our study revealed significant associations between neonatal mortality risk and factors such as maternal age, maternal illiteracy, insurance coverage, pregnancy-related risk factors, high parity (≥ 5 pregnancies), moderate parity (2-4 pregnancies), antenatal care, gestational age, and delays in care-seeking behaviors. These findings emphasize the imperative of implementing targeted interventions to support Afghan mothers and their neonates by enhancing access to comprehensive antenatal care, promoting health literacy, addressing maternal health complexities, and raising awareness about neonatal morbidity risk factors.